2007
DOI: 10.1016/j.smim.2007.04.003
|View full text |Cite
|
Sign up to set email alerts
|

A role for “self” in T-cell activation

Abstract: The mechanisms by which αβ T cells are selected in the thymus and then recognize peptide MHC (pMHC) complexes in the periphery remain an enigmatic. Recent work particularly with respect to quantification of T-cell sensitivity and the role of self-ligands in T-cell activation has provided some important clues to the details of how TCR signaling might be initiated. Here, we highlight recent experimental data that provides insights into the initiation of T-cell activation and also discuss the main controversies a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
41
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 62 publications
3
41
0
1
Order By: Relevance
“…These antagonist ligands are typically altered peptide ligands of the agonist that have a shorter dissociation time 51,53,54 . Interestingly, self-pMHC complexeswhich are expected to have shorter dissociation times than antagonists -have been suggested to act synergistically with the agonist, leading to enhanced T cell responses 55,56 . It is reasonable to assume that within the limit of very short dissociation times, the pMHC complex will no longer interact with the TCR and such null pMHC complexes are expected to have no effect on T cell activation.…”
Section: Altered Peptide Ligandsmentioning
confidence: 99%
“…These antagonist ligands are typically altered peptide ligands of the agonist that have a shorter dissociation time 51,53,54 . Interestingly, self-pMHC complexeswhich are expected to have shorter dissociation times than antagonists -have been suggested to act synergistically with the agonist, leading to enhanced T cell responses 55,56 . It is reasonable to assume that within the limit of very short dissociation times, the pMHC complex will no longer interact with the TCR and such null pMHC complexes are expected to have no effect on T cell activation.…”
Section: Altered Peptide Ligandsmentioning
confidence: 99%
“…However, we note that the mechanism of TCR triggering is controversial and other mechanisms, such as the pseudodimer model in which coreceptors play an important role, have been proposed (Krogsgaard et al, 2007;Choudhuri and van der Merwe, 2007). We will use "MHC1" to refer to an agonist ligand, "MHC2" to refer to either an antogonist ligand or endogenous peptide, and "MHC" to refer to MHC1 and/or MHC2.…”
Section: Model Formulationmentioning
confidence: 99%
“…One of the counterintuitive facets of TCR signaling is that pMHC ligands that bind the TCR nearly as well as agonists decrease its sensitivity to agonists when copresented with otherwise stimulatory ligands, whereas peptides that are far from being agonists increase the sensitivity of T cell responses (Krogsgaard et al 2007). We review here how computer modeling has contributed to our understanding of antagonism and synergism in T cell activation.…”
Section: Antagonism Synergismmentioning
confidence: 99%
“…Consequently, as ligand binding time approaches the agonist threshold, induction of negative feedback increases, directly antagonizing signals coming from neighboring stimulatory ( Synergism (coagonist function) was introduced by the Davis group, who showed that endogenous peptides can increase T cell sensitivity to limiting densities of agonist ligands. Evidence for synergism in TCR signaling is extensive (Krogsgaard et al 2005;Krogsgaard et al 2007;Yachi et al 2007) though not unchallenged (Sporri and Reis e Sousa 2002; Ma et al 2008). One effort to explain and model synergistic effects expanded the TCR-pMHC picture to include intracellular interaction between Lck and the coreceptor (either CD4 or CD8) and extracellular interaction between the coreceptor and the MHC (Li et al 2004), with the coreceptor acting as a bridging molecule.…”
Section: Antagonism Synergismmentioning
confidence: 99%